MEMAHAMI BAHASA INGGRIS DI ICD-10 VOLUME 1 MELALUI ANALISIS SINTAKSIS TENTANG KLAUSA SIFAT - Ari Sukawan (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2017)
Learning English cannot be separated from the four language skills namely Listening, speaking, reading and writing however grammar is also a main thing that must be mastered in English language mastery. Understanding the text content can also be started from the understanding of the language structure in the text. Therefore, this study aims to identify, classify, and analyze the types of clauses used on ICD -10 Volume 1. This study used a qualitative descriptive method which is divided into three stages: preparation, data collection and data analysis. The population in this study is ICD -10 Volume 1 and the sample of this study is ICD -10 Volume 1 chapter I, II, and III. The result studyis according to the theories, on ICD- 10 Volume 1 there are two types of adjective clauses namely restrictive clauses and non-restrictive clauses but most of the adjective clause types is restrictive clause. The result of the study is expected to support all of ICD-10 users in order to understand English sentences on ICD-10 Volume 1 more.